High Availability and Scalability of Mainframe Environments using System z and z/OS as example - Vaupel, Robert (KIT Scientific Publishing, 2013)
Mainframe computers are the backbone of industrial and commercial computing, hosting the most relevant and critical data of businesses. One of the most important mainframe environments is IBM System z with the operating system z/OS. This book introduces mainframe technology of System z and z/OS with respect to high availability and scalability. It highlights their presence on different levels within the hardware and software stack to satisfy the needs for large IT organizations.